Intestinal-mucosa anti-transglutaminase antibody assays to test for genetic gluten intolerance - Quaglia, Sara; De Leo, Luigina; Ziberna, Fabiana; Vatta, Serena; Villanacci, Vincenzo; Granzotto, Marilena; Petix, Vincenzo; Martelossi, Stefano; Di Leo, Grazia; Torelli, Lucio; Not, Tarcisio (Cellular & molecular immunology, 2014)
Celiac disease (CD) is an autoimmune enteropathy characterized by gluten-triggered intestinal mucosa lesions in genetically susceptible individuals carrying the HLA DQ2 or DQ8. CD diagnosis is based on the concentration of IgA serum anti-transglutaminase (anti-tTG) antibodies together with mucosal damage at intestinal biopsy. However, it is now known that in subjects with genetic gluten intolerance, gastrointestinal and extra-intestinal symptoms may be present even when both mucosal morphology and serum anti-tTGs are normal. In this context, the anti-tTG in the intestinal mucosal seem to be the specific CD immunological marker that is detectable before the development of intestinal atrophy and the appearance of serum anti-tTG. This prospective study investigates the presence of intestinal anti-tTG antibodies in patients with differing clinical spectrums of genetic gluten intolerance by using two immunoassays: double immunofluorescence test for anti-tTG on the intestinal mucosa and flow cytometry assay to measure acid-eluted intestinal anti-tTG.